A simple MATLAB/Simulink simulation for PV modules based on one-diode model - Jazayeri, Moein; Uysal, Sener; Jazayeri, Kian (IEEE Computer Society help@computer.org, 2013)
This paper proposes a simple and practical simulation model for solar modules using MATLAB/Simulink. The model is based on a single-diode mathematical model of a solar cell and is capable of accurate modeling of I-V and P-V characteristics of a solar module. Model parameters are obtained from manufacturer's datasheets and series and shunt resistances are calculated using a simple method based on open-circuit voltage, short-circuit current and irradiance values. The model is interfaced with SimPowerSystems toolbox. This feature makes the model capable of being used with power electronic devices and elements for advance analyses. The model is validated using measured I-V characteristics of a commercially available crystalline silicon solar module and the effects of environmental conditions (temperature and irradiance) as well as the effects of cell parameters like series and shunt resistances on module characteristics are investigated. The proposed model is capable of being used by solar energy researchers, system analysts and designers as a simple and helpful tool for advance analysis requirements. © 2013 IEEE.
10th International Conference on High Capacity Optical Networks and Emerging/Enabling Technologies, HONET-CNS 2013 --
Keywords: module characteristics; simulink; solar cell; solar energy; solar module